2020
DOI: 10.3390/w12071968
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Transport Low-Carbon Transitions and the Carbon, Land and Water Footprints of Different Fuel Options in The Netherlands

Abstract: Transport greenhouse gas emissions are mainly caused by the use of fossil fuels, e.g., gasoline and diesel. This case study for The Netherlands calculates how alternative fuels, e.g., electricity, hydrogen or biofuels, contribute to policy aims to decarbonize transport. Alternative fuels, produced in various ways, have different carbon (CF), land (LFs) and water footprints (WFs). This study assesses CFs, LFs and WFs for fuels (kgCO2e/m2/m3 per GJ), showing differences among fuels dependent on primary energy so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The renewables wind, solar and run-of-river hydropower have low unit WFs per amount of energy produced [25,29]. Decarbonisation of the energy system can thereby put extra pressure on water resources [29][30][31][32]. Including the WF of energy input in dietary assessments can thus substantially increase the total WF of a diet.…”
Section: ] •mentioning
confidence: 99%
“…The renewables wind, solar and run-of-river hydropower have low unit WFs per amount of energy produced [25,29]. Decarbonisation of the energy system can thereby put extra pressure on water resources [29][30][31][32]. Including the WF of energy input in dietary assessments can thus substantially increase the total WF of a diet.…”
Section: ] •mentioning
confidence: 99%
“…Even a replacement of only 10% of presently used transport fuels, using the most water efficient biofuels, causes a WF of 60 Gm 3 or 10% of the present EU WF for food and cotton. The recent study of Gerbens-Leenes and Holtz [43] indicated that electricity or hydrogen are favorable to fuel transport, but this will depend on the source of the electricity system. If the electricity comes from large hydropower, the WF may not be so favorable.…”
Section: Water Footprints Of Transportmentioning
confidence: 99%
“…Likewise, given their potential to reduce pollutant emissions, new electric and alternative fuel vehicles have been widely promoted by governments. As the transport sector uses multiple types of energy and is a major source of water consumption from a life-cycle perspective, the environmental water implications of these new types of vehicles should be enhanced [26][27][28]. Finally, over the last decade, artificial intelligence models have seen remarkable advances and successes in many areas of vital importance to our society, including tackling climate change.…”
mentioning
confidence: 99%